High-speed computer for realization of fuzzy arithmetical operations - Корченко, А. Г.; Черныш, Л. Г. (Proceedings of National Aviation University (archive), 1999)
Considered are questions of construction of operating means for realization of fuzzy arithmetic operations. Offered are the structures of devices that perform indicated operations by a method of linear approximating on local maximums